Clinical Significance of Various ELISA Assays for Detecting Antiphospholipid Antibodies - Falcón, C R; Hoffer, A M; Forastiera, R R; Carreras, L O (Thrombosis and Haemostasis, 1990)
We have compared the prevalence of antiphospholipid antibodies (APA) measured by enzyme-linked immunosorbent assay (ELISA), in 119 selected patients using five different antigens: bovine cardiolipin, phosphatidylserine, phosphatidylinositol, bovine partial thromboplastin and human brain partial thromboplastin. All the plasmas have been evaluated for the presence of lupus anticoagulant (LA) activity by clotting techniques. We found a significant association between the incidence of LA and APA (p <0.001), only moderate agreement between the prolongation of the activated partial thromboplastin time (APTT) and ELISAs (r around 0.50) and a good agreement between the ELISAs (r around 0.80). The combination of antibodies against cardiolipin (ACA) and human brain partial thromboplastin (AHPTA) allowed the detection of antibodies in most of the LA positive cases. ACA, AHPTA and antiphosphatidylinositol antibodies detected all the positive samples. Six patients (5%) had a single APA detected. The clinical associations of APA according to phospholipid specificity, immunoglobulin isotype and titer are shown.